Impaired myocardial energetics limits cardiac functional reserve and leads to exercise-induced pulmonary congestion in heart failure with preserved ejection fraction. (14th October 2021) - Burrage, M; Hundertmark, M; Valkovic, L; Watson, W; Rayner, J; Sabharwal, N; Ferreira, V; Neubauer, S; Miller, J; Lewis, A; Rider, O
Abstract: Background: Abnormal cardiac mitochondrial function and energetics may be a unifying feature in the pathogenesis of heart failure with preserved ejection fraction (HFpEF). Transient pulmonary congestion during exercise is emerging as an important determinant of reduced exercise capacity and symptoms in patients with HFpEF. Purpose: We sought to determine if impaired myocardial energetics limits cardiac exercise reserve and leads to exercise-induced pulmonary congestion in HFpEF. Methods: 42 patients across the spectrum of diastolic dysfunction and HFpEF (controls n=10; type 2 diabetes (T2DM) n=9; HFpEF n=14; severe diastolic dysfunction due to cardiac amyloid n=9) (Fig. 1a) underwent assessment of cardiac energetics (myocardial phosphocreatine to adenosine triphosphate ratio, PCr/ATP) and function using cardiovascular magnetic resonance (CMR) imaging and echocardiography, and lung-water using a novel pulmonary proton-density MR sequence. Studies were performed at rest and during exercise (20W for 6 minutes) using a CMR-ergometer. Results: Paralleling the stepwise decline in diastolic function across the groups (E/e' ratio, p<0.0001) was an increase in NT-pro BNP (p<0.0001, Fig. 1b) and reduction in PCr/ATP (control 2.00 [1.86, 2.15], T2DM 1.71 [1.61, 1.91], HFpEF 1.66 [1.44, 1.89], amyloid 1.30 [1.16, 1.53], p<0.0001, Fig. 1c). During exercise, there was progressive blunting of left ventricular (LV) diastolic filling (p<0.0001) (Fig. 2a-b), left atrial (LA) dilatation (p<0.0001), failure of RVEF augmentation (p=0.003), RV-PA uncoupling (RV stroke volume to end-systolic volume (SV/ESV) ratio, p=0.0002), and right atrial (RA) dilatation (p<0.0001) across the groups (Fig. 2b). LV diastolic filling (r 0.41, p=0.008), LA dilatation (r −0.35, p=0.03), RVEF augmentation (r 0.46, p=0.003), RV-PA uncoupling (r 0.36, p=0.02), and RA dilatation (r −0.68, p<0.001) during exercise were strongly linked with impaired myocardial energetics (Fig. 2b). The novel pulmonary proton-density sequence provided images that scaled linearly with water content (validated using a water-doped sponge phantom; r 0.98, p<0.0001), and revealed a progressive increase in lung water signal/pulmonary congestion (Fig. 2c) post-exercise (p<0.0001) across the groups (controls: +0.25% [−1.8, 3.1], p=0.82; T2DM: +0.8% [−1.7, 1.9], p=0.82; HFpEF: +4.4% [0.5, 6.4], p=0.002; amyloid: +6.4% [3.3, 10.0], p=0.004). Pulmonary congestion was associated with impaired LV diastolic filling (r −0.32, p=0.04), RV-PA uncoupling (r −0.39, p=0.01) and RA dilatation (r 0.4, p=0.01) during exercise, and impaired myocardial energetics (r −0.36, p=0.02). Conclusion: A gradient of myocardial energetic deficit exists across the spectrum of HFpEF. This energetic deficit is related to markedly abnormal cardiac exercise responses, which leads to transient pulmonary congestion. The findings support an energetic basis for impaired cardiac reserve and exercise-induced pulmonary congestion in HFpEF. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation